(untitled) (U.S., 2002)
Provides those in the food industry with a comprehensive and authoritative survey of current developments in regulation, research, and best practice in the management of additives in food. Devotes a chapter to antioxidants and discusses preservatives, stabilizers, emulsifiers, and bulking agents.
Keywords: Food,Food industry and trade; Analysis,Safety measures